Knowledge influence on the adaptation to pharmacological recommendations of patients with arterial hypertension - Ilko, Agnieszka; Wudarczyk, Beata; Czyż, Rafał; Jankowska-Polańska, Beata (Journal of Education, Health and Sport, 2018)
Arterial hypertension is a chronic condition that currently affects about 32% of Poles and increases annually. The main factors conditioning the success of treatment is patient-doctor cooperation and adaptation to therapeutic recommendations. Aim of the study was to assess the impact of knowledge on the adaptation to pharmacological recommendations of patients with hypertension. The study involved 102 patients with hypertension. Survey consisted of 38 self-prepared questions and Morisky Medication Adherence Scale (MMAS) and Hypertension Knowledge - Level Scale (HKLS). The group of patient was dominated by people with low levels of adherence. The average level of adherence was reached by 34% of respondents, and the high level was 30%. Women showed a higher level of adherence than men. Patients with low levels of adherence were significantly less likely to have a self-control diary than patients with medium and high levels (p=0.040). The higher level of adherence is, the more participants agrees to the dates of medical appointments. Patients with a high level of adherence never gave up on any of the hypertension drugs. Weakness, as a symptom of too low pressure, was more often mentioned by patients with a high level of adherence than patients with a low level. Patients with medium-level adherence mentioned stroke as a complication of hypertension significantly less frequently than others. The influence of adherence level on hypertensive patients has: gender, keeping a self-control diary, compliance appointments, weakness as a symptom of too low pressure, stroke as a complication of hypertension. There was no significant difference in the level of knowledge of arterial hypertension in groups of patients with different levels of adherence.